Respon Pertumbuhan dan Hasil Bawang Merah di Lahan Gambut terhadap Jenis Mulsa dan Pemupukan NPK - Agustina Anci Putri; Radian; Tatang Abdurrahman (J-Plantasimbiosa, 2026)
Shallots, as a horticultural commodity, have great potential for development. Efforts to develop shallots require technology to provide a growing environment that meets the necessary growth conditions. The use of mulch is expected to help maintain soil moisture and reduce evaporation rates, thereby meeting the plant's water requirements. The addition of nutrients through fertilization is also expected to improve shallot productivity on peatland. This study aims to examine the interaction between the use of mulch and NPK fertilization doses in increasing agricultural yields on peatland. This research used a factorial randomized block design (RBD) with two treatment factors. The first factor was the type of mulch, consisting of four levels: no mulch (M0), rice straw (M1), black silver plastic (M2), and weed mat (M3). The second factor was the dose of NPK fertilization, which consisted of four treatments: urea 350 kg/ha, SP-36 250 kg/ha, KCL 150 kg/ha (P1); urea 300 kg/ha, SP-36 200 kg/ha, KCL 100 kg/ha (P2); urea 250 kg/ha, SP-36 150 kg/ha, KCL 100 kg/ha (P3); and urea 200 kg/ha, SP-36 100 kg/ha, KCL 90 kg/ha (P4). Each treatment was repeated three times. The research results show that the interaction of the two factors affects the relative growth rate during the 1-2 weeks after planting, 3-4 weeks after planting, the number of leaves, dry weight of the plant, the number of tubers per clump, the weight of tubers per clump, and the dry tuber weight per clump. The treatment of straw mulch and high-dose fertilizer application produced better results compared to the other treatments